2019
DOI: 10.1021/acscatal.9b03544
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Deposited Amorphous Zn-Doped NiFeOxHy for Enhanced Water Oxidation

Abstract: Although NiFeO x H y has attracted enormous attention as an alkaline water electrolyzer owing to its high performance in the oxygen evolution reaction (OER), it still requires further improvement in terms of catalytic activity, durability, and an underlying understanding of the mechanism. Here we report the fabrication of Zn-doped NiFeO x H y (Zn;NiFeO x H y ) that has advanced electrocatalytic activity and stability in comparison to pure NiFeO x H y in the OER via simple chemical bath depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…The onset potential of Ni oxidation peak gradually decreases (inset of Figure 2 a), accompanying the cathodic peak shifts negatively (Δ E P,C =−94 mV), which suggest that the active species (Ni 3+ ) form at a lower potential [28] . It was reported that the phosphates can be easily exchanged with hydroxide anions [3a, 29] . As for pure amorphous triMPO 4 (Figure 2 b), both the cathodic peak shift (Δ E P,C =−34 mV) and the onset potential of Ni oxidation peak shift become smaller than those of glass‐ceramic under the same conditions.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The onset potential of Ni oxidation peak gradually decreases (inset of Figure 2 a), accompanying the cathodic peak shifts negatively (Δ E P,C =−94 mV), which suggest that the active species (Ni 3+ ) form at a lower potential [28] . It was reported that the phosphates can be easily exchanged with hydroxide anions [3a, 29] . As for pure amorphous triMPO 4 (Figure 2 b), both the cathodic peak shift (Δ E P,C =−34 mV) and the onset potential of Ni oxidation peak shift become smaller than those of glass‐ceramic under the same conditions.…”
Section: Resultsmentioning
confidence: 89%
“…Recent studies reported that cations or anions in catalysts could leach into the electrolyte under alkaline OER conditions, for examples, Sn 4+ leaching from CoSn 2, [31] CoSn(OH) 6 [32] and SnNiFe hydroxide perovskite, [33] Zn 2+ leaching from Zn‐Ni‐Co spinel oxides, [34] and F − leaching from NiFe‐OH‐F [16] . In addition, phosphates can be easily exchanged with hydroxide anions during the electrochemical process [3a, 8a] . Generally, the ion leaching behaviors can trigger favorable OH − adsorption on catalyst surface to accelerate the OER [13b]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 Very recently, the positive effect of Zndoping on OER activity in alkaline media has been independently reported for the case of NiFeO x H y . 69 Of course, optimum doping levels and mechanistic considerations will depend on the structure and electronics of other host matrices. Such studies are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that metal (oxy)hydroxides serve as promising OER catalysts. [ 14 ] Accordingly, we deduce that the rational design of antiperovskite/(oxy)hydroxide hybrid with abundant active sites and high conductivity may offer an opportunity for the application of water splitting. However, due to the demanding conditions required for heterostructure synthesis, [ 15 ] a simple synthetic process for antiperovskite/(oxy)hydroxide hybrid system is greatly valuable.…”
Section: Introductionmentioning
confidence: 99%